2007
DOI: 10.1002/pat.974
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and humidity sensing properties of synthesized hydrophosphoric acid doped polyaniline

Abstract: H3PO4 doped polyaniline was synthesized by a single‐step chemical polymerization method using ammonium persulfate as an oxidizing agent. The material characterization was done by SEM, UV–vis spectroscopy and thermogravimetric analysis (TGA). The pellets of the synthesized material were used to study the electrical properties, using a four‐probe method. The room temperature electrical conductivity is found to be 0.2201 S/cm. The electrical resistance in response to the varying humid environment (ranging between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In additionally, inhibition zones increase with increasing amount of tested sample and this case is in agreement with the literature [20,33]. When the antimicrobial activity results of the monomer and polymer were compared to findings reported in the literature [34], it was observed that the synthesized compounds exhibited good antibacterial activity and they have potential usage as antibacterial agent.…”
Section: Antimicrobial Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…In additionally, inhibition zones increase with increasing amount of tested sample and this case is in agreement with the literature [20,33]. When the antimicrobial activity results of the monomer and polymer were compared to findings reported in the literature [34], it was observed that the synthesized compounds exhibited good antibacterial activity and they have potential usage as antibacterial agent.…”
Section: Antimicrobial Propertiessupporting
confidence: 91%
“…It can be seen from figure that the conductivity of the P(4-MMAP) increased remarkably with the increase in doping time at each temperature, but then stabilized. The increase in the conductivity with temperature is typical for conductive polymers, and this situation is defined as 'thermally activated behavior', in the literature [33]. It can be explained by the increase in the charge transfer efficiency between the polymer chains and the mobility of I 3 dopant anions with temperature [16,33].…”
Section: Doping With Iodinementioning
confidence: 99%
“…The increase in conductivity of P(2‐MBAP) after doping with I 2 by increasing the temperature is similar to that of conductive polymers. This could be explained by the increase in charge transfer efficiency between polymer chain and I 3 − dopant anions with temperature …”
Section: Resultsmentioning
confidence: 99%
“…Existing chemieresistors are made of conductive polymers (CPs) [7][8][9][10] or metal oxides [11,12]. Metal oxides can detect concentrations of parts per billion (ppb) but operate at elevated temperatures of about 200-300 • C and possess limited selectivity to gases.…”
Section: Introductionmentioning
confidence: 99%